On the use of vocabularies of geometric forms in ornamental pattern design. Issue 1 (1st August 2019) - Hindocha, Ameet
This article examines the development and use of vocabularies of shapes constructed using geometric principles as a basis for ornamental pattern design. Through a combination of digital fabrication techniques and printmaking, I have developed a process for freely exploring geometric ornamentation based on compatible vocabularies of shapes. The process highlights the correlation between the use of these vocabularies and language as a medium of expression. It can also provide an insight into how the universality of the visual expression of mathematical concepts helps us perceive the nature of the world around us.